2021
DOI: 10.3390/ijerph18073767
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of COVID-19 Pandemic during the First Wave (Feb–May 2020): A Cross-Sectional Study among Italian Healthcare Workers

Abstract: Italy was the first country in Europe to face the coronavirus pandemic. The aim of the study was to analyze healthcare workers’ (HCWs) level of information, practice, and risk perception towards COVID-19. We set up a cross-sectional study through SurveyMonkey® and distributed the link through Facebook and Whatsapp closed groups. The research instrument was a 31 items questionnaire distributed using Facebook and Whatsapp. It was conducted in Italy from February to May 2020. The study participants were general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The leading role in shaping public opinion on the risks associated with the pandemic and the necessary protective measures is assumed by health workers [32], including medical students, as one of the main segments of the population who can lead by example in the formation of an active civil attitude of the population for the prevention of infection. According to Italian researchers, healthcare workers have a sufficient level of information regarding the risks associated with the spread of COVID-19, and they actively use measures of nonspecific protection [33]. Earlier, we conducted a pilot study of medical students' knowledge and attitudes to the face mask regime [34], which showed that most respondents were civically responsible, understood the importance of using face masks to protect others, and could actively promote their use to the public.…”
Section: Introductionmentioning
confidence: 99%
“…The leading role in shaping public opinion on the risks associated with the pandemic and the necessary protective measures is assumed by health workers [32], including medical students, as one of the main segments of the population who can lead by example in the formation of an active civil attitude of the population for the prevention of infection. According to Italian researchers, healthcare workers have a sufficient level of information regarding the risks associated with the spread of COVID-19, and they actively use measures of nonspecific protection [33]. Earlier, we conducted a pilot study of medical students' knowledge and attitudes to the face mask regime [34], which showed that most respondents were civically responsible, understood the importance of using face masks to protect others, and could actively promote their use to the public.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, instead of learning new knowledge and skills, care professionals might have utilized previous knowledge and skills in the care to a larger extent than staff in management or coordination positions. To some extent, this is supported by findings from Italy during the first wave in early spring 2020, where care professionals despite the challenges managed to cope with the situation relying on previous knowledge and skills [ 37 , 38 , 39 , 40 ]. Despite not being directly responsible for the clients’ care, from the managers/coordinators perspective, they faced many challenges and demands in their professional roles and tasks, i.e., the demands for crisis management skills were most prominent in this staff category.…”
Section: Discussionmentioning
confidence: 70%
“…On 12 March 2020, shortly after the first confirmed SARS-CoV-2 infections, a national strategy for the COVID-19 response was developed and restrictive measures (e.g., national lockdown) were implemented; each region and related public health services developed specific plans according to the allocated resources, facing severe difficulties in fighting an unprecedented healthcare emergency [23,24]. HCWs found themselves to be at high risk of infection and of infecting a family member, to be inadequately informed and unprepared to face the COVID-19 pandemic and experiencing mental health issues [25,26].…”
Section: The Italian Contextmentioning
confidence: 99%